Decision Support System Determination Of Achieving Students Using The Promethe Method At Smk Negeri 4 Kepahiang - Jepri Haji Utama; Liza Yulianti; Dewi Suranti (Jurnal Media Computer Science, 2022)
SMK Negeri 4 Kepahiang is one of the State Vocational High Schools located in Kepahiang Regency, Bengkulu Province. So far, the assessment system for outstanding students in schools is carried out by registering students and looking at 4 aspects of the assessment, namely the value of knowledge, the value of absenteeism, the value of non-academic achievement, the value of attitudes and behavior. The determination process is still done manually, where the four aspects will be compared between one student and another so that it can be known with various considerations, so that 3 outstanding students are obtained from the number of students. This is of course an obstacle for the school, because sometimes it is difficult to determine outstanding students and it takes quite a long time. The Decision Support System for determining outstanding students at SMK Negeri 4 Kepahiang was made using the Visual Basic .Net programming language and SQL Server 2008r2 database, where in the application one of the Decision Support System Methods (SPK) was applied, namely the Promethee Method. This application can be used as an alternative in assisting the school in determining outstanding students each academic year. The Decision Support System for determining outstanding students at SMK Negeri 4 Kepahiang begins with student assessment data which is then processed into the Promethee Method according to the stages of the method, so as to produce a final score by sorting the highest score to the lowest value. Based on the assessment data for the 2021/2022 Academic Year as many as 4 students, the outstanding student was Alim Predika with a net flow value of 0.42..